A Glycolipid Adjuvant, 7DW8-5, Enhances the Protective Immune Response to the Current Split Influenza Vaccine in Mice - Feng, Huapeng; Nakajima, Noriko; Wu, Li; Yamashita, Makoto; Lopes, Tiago J. S.; Tsuji, Moriya; Hasegawa, Hideki; Watanabe, Tokiko; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2019)
Vaccination is an effective strategy to control influenza disease. Adjuvants enhance the efficacy of vaccines, but few adjuvants are approved for human use, so novel, safe, and effective adjuvants are urgently needed. The glycolipid adjuvant 7DW8-5 has shown adjuvanticity to malaria vaccine; however, its adjuvant effect for seasonal influenza vaccine remains unknown. Here, we evaluated the adjuvanticity of 7DW8-5 to a quadrivalent split influenza vaccine in a mouse model. 7DW8-5 significantly enhanced virus-specific antibody production when administrated with influenza vaccine compared with that of vaccine alone; 10 μg of 7DW8-5 induced similar antibody levels to those induced by alum. Mouse body weight loss was reduced and, notably, the survival rate was increased in the vaccine plus 7DW8-5 group compared with that in the vaccine plus alum group. Our results indicate that the glycolipid 7DW8-5 is a promising adjuvant for influenza vaccine.